Simulation of interest coordination of economic subjects in housing construction - N. N. Shelomentseva; O. V. Grushina; T. A. Krasnoshtanova (Мир новой экономики, 2023)
In the present paper, the consequences of the introduction of project financing against the backdrop of crises in 2020 and 2022 are analyzed. The subject interactions in the course of housing construction under the conditions of project financing are considered. A multi-criteria economic-mathematical model for the interest coordination of economic subjects in housing construction has been proposed. The model permits to understand and evaluate the economic consequences of choosing the possible options from the standpoint of each of the economic subjectss. The numerical calculations of choosing two (in pairs), and all three (developer, bank and consumer) economic subjects were performed using the proposed multi-criteria model with the stated limitations. The MATLAB software was employed to solve optimization problems and plotting. The solutions acceptable to the subjects were chosen from a set of Pareto-optimal alternatives. Despite the fact that all subjects of housing construction are involved in the interaction, this interaction does not occur simultaneously, but in a complex subordinate manner: the bank took the dictating position in project financing, and the consumer pays for everything. The state should play a role of the subject, which should coordinate the interests of the developer, the bank and the population. The task of the state is to create such conditions in the housing construction market so that economic subjects are interested in coordination of their interests to find a compromise. This opens routes for further research.